Thiazolyl and Isothiazolyl Azomethine Derivatives with Anti-inflammatory and Antioxidant Activities - Geronikaki, Athina; Vicini, Paola; Incerti, Matteo; Hadjipavlou-Litina, Dimitra (Arzneimittelforschung, 2004)
Several thiazolyl/benzothiazolyl/benzo [d] isothiazolyl Schiff bases and hydrazones have been tested as anti-inflammatory agents and five new compounds have been synthesized. The anti-inflammatory activity was examined in vivo using the carrageenin induced mice paw edema test (inhibition 16.3–64 %). The compounds were tested for antioxidant activity as hydroxyl scavengers and for their ability to interact with the stable free radical 1,1-diphenyl-2-picryl-hydrazyl (DPPH). Both anti-inflammatory and antioxidant activities depended on some structural characteristics of the synthesized compounds.
Keywords: Hydrazones, anti-inflammatory activity, antioxidant activity; Isothiazolyl azomethine derivatives, anti-inflammatory activity, antioxidant activity, QSAR studies; Schiff bases; Thiazolyl azomethine derivatives, anti-inflammatory activity, antioxidant activity, QSAR studies